ANALISIS COMMON SIZE STATEMENT DAN RASIO KEUANGAN UNTUK MENILAI KINERJA KEUANGAN SEKTOR INDUSTRI ROKOK YANG TERCATAT DI BEI (PERIODE TAHUN 2015-2017) - Nihayah Saefil Ikhsan; ronny Malavia Mardani; Budi Wahono (UNIVERSITAS ISLAM MALANG, 2019)
ABSTRACTThe aim of this study was to analyze and to describe the common size and financial ratio analysis of financial performance of cigarette companies listed on the Indonesia Stock Exchange. Population in this study. The population in this study were cigarette companies listed on the IDX for the period 31 December from 2015-2017. This research technique uses judgment sampling because the sample used in this study with the criteria of the company provides complete financial statements for the period 31 December from 2015-2017. The source of this research data is in the form of annual data contained in the financial statements of cigarette industry companies for the period 2015-2017 obtained from the official website of the Indonesia Stock Exchange www.idx.co.id The analytical method used in this study is descriptive with a quantitative approach in the form of.The results of the study show that: Common Size Balance analysis which has not much different analysis results is PT. Gudang Garam Tbk and PT. Wismilak Inti Makmur Tbk. For Analysis of Common Size Profit and Loss shows that PT. Gudang Garam Tbk, a company that dominates more than the other three companies. While financial ratio analysis (1) Liquidity in all four companies is dominated by PT. Wismilak Inti Makmur Tbk which (2) Profitability is dominated by PT. Gudang Garam Tbk where it has fluctuations with increasing returns (3) Activities at the results of this ratio are dominated by PT. Gudang Garam Tbk which is more stable and more effective, (4) Solvability from the results of the study shows that the performance of PT Gudang Garam Tbk is better.Keywords: Common Size Analysis, Financial Ratio and Financial Performance